Telomere fusion threshold identifies a poor prognostic subset of breast cancer patients. Issue 6 (25th February 2015) - Simpson, K.; Jones, R.E.; Grimstead, J.W.; Hills, R.; Pepper, C.; Baird, D.M.
Abstract : Telomere dysfunction and fusion can drive genomic instability and clonal evolution in human tumours, including breast cancer. Telomere length is a critical determinant of telomere function and has been evaluated as a prognostic marker in several tumour types, but it has yet to be used in the clinical setting. Here we show that high‐resolution telomere length analysis, together with a specific telomere fusion threshold, is highly prognostic for overall survival in a cohort of patients diagnosed with invasive ductal carcinoma of the breast (n = 120). The telomere fusion threshold defined a small subset of patients with an extremely poor clinical outcome, with a median survival of less than 12 months (HR = 21.4 (7.9–57.6), P < 0.0001). Furthermore, this telomere length threshold was independent of ER, PGR, HER2 status, NPI, or grade and was the dominant variable in multivariate analysis. We conclude that the fusogenic telomere length threshold provides a powerful, independent prognostic marker with clinical utility in breast cancer. Larger prospective studies are now required to determine the optimal way to incorporate high‐resolution telomere length analysis into multivariate prognostic algorithms for patients diagnosed with breast cancer. Highlights: High‐resolution telomere length analysis is highly prognostic for overall survival. Independent of ER, PGR, HER2 status, NPI and grade. Dominant variable in multivariate analysis.